Lipid droplet-free nanovesicles extruded from stromal vascular fraction improve adipocyte regeneration in the centre of dermal graft - Yuyang Zeng; Di Sun; Rongrong Wang; Ran An; Jiaming Sun; Jie Yang (Stem Cell Research & Therapy)
Abstract Background The stromal vascular fraction (SVF) has been validated for enhancing tissue regeneration because of its concentration of multipotent cells and growth factors, and for mitigating inflammatory response due to its elimination of the majority of lipid droplets. However, it is difficult for fresh SVF to maintain bioactivity for a long period, and the loss of numerous tangible masses during preparation limits its application in repairing large volume defects. Here, we fabricated a self-assembly nanovesicle extruded from SVF (SVF-EVs) by mechanical shear and co-transplanted it with dermal microparticles to verify its potential for repairing large volume defects. Methods The SVF-EVs were prepared by removing the oil from adipose tissue followed by sequentially extruding SVF through membrane filters. The lipid content of SVF-EVs was compared with SVF using Oil Red O staining. The morphology and adipogenic-related protein of SVF-EVs were characterized. The pro-adipogenic potency of SVF-EVs in vitro was determined using Oil Red O staining of ADSCs, western blot, and qRT-PCR. In vivo, dermal particle grafts mixed with SVF-EVs were subcutaneously transplanted in nude mice and harvested after 4 and 6 weeks. By examining the weight and volume of grafts and histological staining, we explored the effect of SVF-EVs on adipose tissue regeneration and anti-inflammatory ability. Results Our results showed that the removal rate of proceeding of SVF-EVs could remove 75.07 ± 2.80% lipid in SVF. The SVF-EVs displayed 100 ~ 150 nm sphere vesicles and contained pro-adipogenic protein. In vitro, SVF-EVs promote the synthesis of lipids in ADSCs. Besides, after co-transplanting of SVF-EVs, adipose regeneration was detected in vivo in the dermal particle grafts. Conclusions These findings revealed that extruding SVF into nanovesicles can effectively reduce the implantation of lipid droplets that cause inflammation, and co-transplanting SVF-EVs with dermal microparticles may be a considerable strategy for large volume defects repair.